ANALYSIS OF HIGH-SPEED RUNNING AND SPRINT RUNNING IN ELITE FEMALE FOOTBALL COMPETITIONS - Oana-Ruxandra Stîncel; Cristian Lazăr; Vlad Nicoară; Mihaela Oravițan (ALTIUS ACADEMY Foundation - Faculty of Physical Education and Sports, 2021)
Introduction: Although football is recognized as the fastest growing sport globally, scientific literature on female footballis still limited. Available published data in understanding the physical demands of female football players have described the necessity of a high level of physical conditioning during matches with average heart rates of 84-86% maximum heart rate and an average of 9.1-11.9 km in total distance covered in the running. The most commonly utilized physical performance measures reported are high-speed running (19km/h-23km/h) and sprinting (>23 km/h). A better understanding of football's physical, technical and tactical demands has resulted from investigations of both training and matches by wearing a global positioning system unit.Objective: This study aimed to assess the running speed and the proportions of different types of running during official competitions in elite female football players.Material and Method: A total of 22 female players (16 seniors and six juniors) that are part of a Romanian First League female football team -Politehnica Timisoara, have been monitored for running speed and covered distance in 6 official matches, which represent a quarter of the championship period. The assessment period was ten weeks (August-October 2021). The monitored parameters (total distance, distance/minute, low speed running, high speed running, sprint running, and maximum speed) wereobtained using K-Sport GPS with a high sampling rate of 50 Hz.Results: During the six analyzed matches the following average values were found: total covered distance -7906.33 ± 1176.68 m, distance/minute -90.83 ± 3.72 m/min, low-speed running distance-7598.50 ± 1102.16 m, high-speed running distance -308 ± 101.31 m, sprint running distance -69.50 ± 28.54 m, and maximum speed -25.13 ± 0.84 km/h.Conclusion: Regarding the monitored parameters (total distance, average speed, proportion of different speed running, maximum speed), we observed a constancy between different matches. During female football matches, high-speed running and sprinting covered 4.77% of the total distance. Based on this data, a future training objective would be the enhancement of this percentage in order to optimize the key moments of the matches